Procedural invariance as a result of commitment costs: evidence from an economic experiment on farmers' willingness to pay for digestate. Issue 15 (2nd September 2019) - Pappalardo, Gioacchino; Selvaggi, Roberta; Lusk, Jayson L.
ABSTRACT: We offer a conceptual explanation for some of the procedural invariance witnessed in experimental studies related to the concept of commitment costs, which is confirmed in a field experiment with Sicilian farmers valuing a renewable soil conditioner.